Wait for signs : twelve Longmire stories - Johnson, Craig, 1961-; Johnson, Craig, 1961- (New York : Viking, 2014)
Twelve Longmire short stories available for the first time in a single volume-featuring an introduction by Lou Diamond Phillips of A&E's Longmire. Ten years ago, Craig Johnson wrote his first short story, the Hillerman Award- winning "Old Indian Trick." This was one of the earliest appearances of the sheriff who would go on to star in Johnson's bestselling, award-winning novels and the A&E hit series Longmire. Each Christmas Eve thereafter, fans rejoiced when Johnson sent out a new short story featuring an episode in Walt's life that doesn't appear in the novels; over the years, many have asked why they can't buy the stories in book form. Wait for Signs collects those beloved stories-and one entirely new story.
Keywords: Longmire, Walt (Fictitious character) -- Fiction; Sheriffs -- Wyoming -- Fiction; Mystery fiction